A metabarcoding tool to detect predation of the honeybee Apis mellifera and other wild insects by the invasive Vespa velutina - Verdasca, Maria João (2022)
The invasive Vespa velutina has been widely referred as an effective predator of honeybees. Despite the potential risk to pollination services provision and honey production, there is no accurate quantification and assessment of its real consequences for honeybees. To date, the identification of the honeybee and other insects in the diet of V. velutina has been investigated by direct observation of adult foraging or examination of food pellets. To overcome these limitations, in this study we used a DNA metabarcoding approach to evaluate the usefulness of different types of sample (jaws and stomachs collected from workers and larval faecal pellets taken from the hornet comb) to investigate the predation of V. velutina upon honeybees, and potentially on other insects. Honeybee DNA was identified in all types of samples, but larval faecal pellets retrieved the higher number of reads of honeybee DNA and the largest diversity at all taxonomic levels. Over all samples we could identify 4 orders, 9 families, 6 genera and 1 species of prey. We estimate that collecting 6 workers is sufficient to identify honeybee predation by a colony using worker’s jaws. Stomachs were the least useful sample type to detect honeybee DNA. The presence of honeybee DNA in all analysed colonies irrespective of collection site, and the variety of insect orders detected in the diet support current concerns over the acknowledged negative impact of V. velutina on managed honeybees and its potential threat to pollination services provision.